Evaluation of Radiological and Neurological Outcomes after Anterior Cervical Corpectomy with Fusion using Expandable Cage Alone and Expandable Cage with Anterior Cervical Plating - Seervi, Manoj Kumar; Jain, Surendra; Purohit, Devendra Kumar; Meena, Ugan Singh (Asian Journal of Neurosurgery, 2023)
Objective After anterior cervical corpectomy expandable cage were used with or without using anterior cervical plate for structural support are being preferred over autologous bone graft and other types of cages. Nowadays, the preferable type of cages and application of anterior cervical plate remain a debatable topic with studies giving divergent results. The purpose of this study is to evaluate the outcomes of expandable cages used alone or expandable cage used with anterior cervical plate following anterior cervical corpectomy.Materials and Methods This study was conducted on 100 patients from January 2019 to December 2021 and all patients were undergone anterior cervical corpectomy and fusion and divided in two groups with expandable cage only (Group A) and expandable cage with anterior cervical plate (Group B). Various long-term benefits and radiological outcomes were studied in both groups.Statistical Analysis and Results In this study, 100 patients were included and all patients underwent corpectomy followed by insertion of expandable cage alone or with anterior cervical plate. There was an improvement in C2–C7 Cobb's angle in group B was significantly higher than group A (p < 0.05) and decrease in Nurick's scale score in group B was significantly higher than group A (p < 0.05). The outcomes were measured with fusion rate (94%), subsidence rate (15%) and change in C2–C7 Cobb's angle was 4 degrees in this study.Conclusion Expandable cage with or without anterior cervical plate was used after anterior cervical corpectomy for various cervical pathological conditions. In this study, we conclude the long-term benefits and radiological outcomes of two groups as expandable cage was used alone or with additional application of anterior cervical plate. In this study, the results were more in favor of additional application of anterior cervical plate as compared with expandable cage alone and more studies were required in future for more established long-term benefits and drawbacks.
Keywords: cervical corpectomy; expandable cage; anterior cervical plate; radiological outcomes